IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK PADA BIRO ADMINISTRASI PIMPINAN - Syahrial, Helsa; Rahayu, Sri; Dosinta, Nina Febriana (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This research is conducted to find out how to implement the public information transparency of Biro Administrasi Pimpinan that corresponds with UU Nomor 14 Tahun 2008. This research using a descriptive qualitative method. The data collection method is an interview method. With the two-count informan Kepala Bagian Materi Komunikasi dan Pimpinan and Kepala Sub Bagian TU. The research shows that Biro Adminitrasi Pimpinan has been implementing information according to UU Nomor 14 Tahun 2008, the information about leadership activities can be seen on the social media Biro Administrasi Pimpinan and application SIAP KALBAR although there are still such obstacles as tge tools and infrastructure that sometimes lack of the coverage of executive activities and for the future management Biro Administrasi Pimpinan plans to provide the media center for interactive dialog activities.